Differential Pulse Polarographic Determination of Selenium(IV) Using 3,4-Diaminobenzoic Acid - Inam, Recai; Yilmaz, Emine; Icin, Hayriye (Asian Journal of Chemistry, 2010)
In the polarographic determination of Se(IV), the most serious interfering elements were indicated to be Pb(II) and Cd(II) due to their surface reaction with selenium on mercury drop electrode. Since the piazselenols formed by the reaction of Se(IV) with 5-carboxy-1,1,3-benzoselenadiazole (4-carboxypiazselenol), differential pulse polarography based on the adsorption of 4-carboxy piazselenol on the mercury electrode gave a very sensitive peak at – 0.12 V (vs. SCE) and this overcame interference by Pb(II) and Cd(II). 4-Carboxy piazselenol was reduced as the adsorbed compound and the peak current was large enough to have better sensitivity than the ordinary reduction process for Se(IV). The proposed method based on this new peak showed good reproducibility and accuracy with a relative standard deviation of 1.19% and relative error of ±0.80% for the determination of 5.0 x 10–6 M Se(IV) next to 1.0 x 10–5 M Pb(II). There is a linear relationship between the differential pulse polarography peak current and the Se(IV) concentration over the range 1.0 x 10–7 – 1.0 x 10–4 M with a correlation coefficient of 0.9958. The method was applied to synthetic samples containing known amounts of Se(IV) next to known amounts of interfering ions with different ratios and probabilities.